Where are the Integration Policies Successful? Explaining Immigrants’ Integration in Europe with Multi-Dimensional Measures - Monica Roman; Smaranda Cimpoeru; Elena-Maria Prada; Ioana Manafi (Statistika: Statistics and Economy Journal)
The paper aims to assess and explain the multidimensional integration of migrants in Europe by addressing two research questions: (1) Are there differences between European countries regarding migrants’ integration? and (2) What individual characteristics might explain differences in integration levels? To answer the research questions, an Aggregate Integration Index was built, based on four partial integration indexes, covering social, psychological, political and economic dimensions of integration. The paper uses individual data for third country nationals residing in Europe, extracted from the European Social Survey (2018), and relies on a multistage methodology, using factor analysis for deriving various integration measures and multivariate regressions. The results show that in all the European countries in the sample, migrants’ integration is still relatively low and there is room for improving their situation. At the same time, the integration policies seem to be effective: in countries with more inclusive integration policies, individuals feel better integrated.